Efficacy of Nalbuphine in Restraining Oxytocin-Induced Discomfort During Operative Delivery - Andleeb, Munnaza; Raja, Ayisha; Sharif , Fatima; Majeed, Kaukab; Ansari , Kaswar Sajjad; Surayya Jabeen, Syeda (Pakistan Armed Forces Medical Journal, 2026)
Objective: To measure the intensity of pain caused by bolus of Oxytocin during cesarean delivery and efficacy of Nalbuphine to control it. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital Quetta, Pakistan from May to October 2023. Methodology: This Quasi-experimental study was conducted in CMH Quetta for a duration of six months (May-October 2023). The ethical board of hospital granted permission (ERC#CMH QTA-IERB/09/2023). Total 150 patients were included in the study after application of inclusion and exclusion criteria. Patients were divided into two groups marked as: Group-S (n=75) and Group-N (n=75). The Group-S patients did not receive Nalbuphine and Group-N patients received Nalbuphine. The primary outcome was frequency of side effects in both groups and secondary outcome was patient’s satisfaction. Results: The frequency of adverse effects in Group-S was higher than the Group-N patients. The most frequent side effect was chest pain with the frequency of 16(21.3%) in Group-S patients and 2(2.7%) in Group-N patients with p value of <0.001. The patient satisfaction was better in Group-N patients. The frequency of patient satisfaction was 72(96.0%) in Group-N patients and 47(62.7%) in Group-S patients with p-value <0.001. Conclusion: Nalbuphine can mitigate discomfort due to Oxytocin bolus in parturient undergoing cesarean section under Centro-axial anesthesia.